E-Instructional Multimedia in Basic Concepts of Electrical and Electronic Lessons - Budiastuti, Pramudita; Khairudin, Moh.; Azman, M.N.A (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Interactive learning media facilitate students to be understand and comprehend certain contents of engineering subjects. Therefore, this study aimed to develop e-instructional multimedia for students in the subject of basic electronics and electricity using adobe flash CS 5.5. This subject was selected to support the teaching-learning process at the Vocational Secondary Schools. There were five stages during the development of the learning media, including (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation (ADDIE). Furthermore, 30 students in total were selected to test the media practicability. The results revealed that this multimedia is acceptable based on five criteria: creativity, affectivity, efficiency, interestingly, and interactivity with the scores of 76.8, 76.8, 71.5, 77.4, and 74.4 respectively. This study suggested the implementation of the e-instructional multimedia for further understanding its empirical application.